Cortical Gray Matter Injury in Encephalopathy of Prematurity: Link to Neurodevelopmental Disorders - Fleiss, Bobbi; Gressens, Pierre; Stolp, Helen B. (Frontiers in Neurology, 2020)
Preterm born infants frequently suffer from an array of neurological damage, collectively termed Encephalopathy of Prematurity (EoP). They also have an increased risk of presenting with a neurodevelopmental disorder (e.g. autism spectrum disorder; attention deficit hyperactivity disorder) later in life. It is hypothesised that it is the grey matter, in addition to white matter, injury to the cortex in EoP that is responsible for the altered behaviour and cognition in these individuals. However, the grey matter injury that occurs in infants following preterm birth is still not fully elucidated. Here we will review the current state of knowledge in this field, amalgamating data from both clinical and preclinical studies. This will be placed in the context of normal processes of developmental biology and the known pathophysiology of neurodevelopmental disorders. Novel diagnostic and therapeutic tactics required integration of this information so that in the future we can combine mechanism based approaches with patient stratification to ensure the most efficacious and cost-effective clinical practice.